Formulação p. adaptativa do método dos elementos de contorno aplicado a problemas de potencial - Willmersdorf, Ramiro Brito (1988)
This work is concerned with the development of the p-adaptive version of the boundary element method applied to bidimensional steady state potential problems. In the p version of automatic refinement, hierarquical shape functions are selectively inserted in the discretization, complying with error analysis. Some potential problems are solved with this technique and the results are compared to analytical and numerical solutions.